A comparison of paralindelof type properties in bitopological spaces - Bouseliana, Hend; Kilicman, Adem (Natural Sciences Publishing, 2015)
An implication of (i, j)-paralindelof spaces with (i, j)-normal and (i, j)-collectionwise normal space has been studied. We introduce the new definitions of the normal concept in bitopological setting namely (i, j, j)-normal spaces and (i, j)j-normal spaces. When the pairwise paralindelof space implies pairwise Lindelof is investigated. Furthermore, the concepts of para-m-Lindelof and m-Lindelof have been extended to bitopological setting. Also, we study the relation of (i, j)-para-m-Lindelof and (i, j)-m-Lindelof.